Pendampingan Inovasi Pembuatan Mie Pelangi melalui Gerakan Gemar Makan Sayur dan Buah di Wilayah Kerja Puskesmas Kelayan Timur - Agustina, Norsita; Indah, Meilya Farika; Chandra, Chandra; Asrinawaty, Asrinawaty; Rahman, Eddy (Universitas Baiturrahim, 2025)
Noodles are the second most consumed staple food in Asia after rice. Excessive consumption of noodles has a negative impact on health. Based on data, the consumption of instant noodles by Indonesian people is the second largest in the world after China. The purpose of this Community Service activity is to increase knowledge related to healthy food and how to make healthy food with vegetables and fruits, especially noodles based on vegetables and fruits. In addition, this activity also aims to increase fruit and vegetable consumption patterns for children who have difficulty eating vegetables and fruits in this case is a new innovation product, namely noodles made from fruit and vegetables for representatives of each cadre in the Kelayan Timur Health Center work area of ​​Banjarmasin City. The method used in this Community Service is a demonstration. A total of 10 representatives of active posyandu cadres became participants involved in this activity from beginning to end. The results of the community service activity were that all participants were enthusiastic in implementing the activity and this activity was carried out pre and post tests so that they could find out the impact of consuming instant noodles on children and partners could have the skills to make rainbow noodles made from vegetables and fruits. The conclusion of this activity is that partners experience increased knowledge and skills in making healthy noodles for consumption by families and can be developed as a business.